An Empirical Investigation of Initial Public Offerings (IPOs) Underpricing in China’s A Share Market - Wang, Ying (2009)
Abstract Many papers have documented that China presents the highest level of initial public offerings (IPOs) in the world. This paper aims to test the existence of IPO underpricing in China’s stock market and find the effected variables to explain this abnormal phenomenon. Many theories and hypothesis are advocated based on the investigations of developed stock market, which include winner’s curse, ex-ante uncertainty, signalling model, underwriter reputation, cascade hypothesis and so on. I study whether these theories and hypothesis are suitable for explaining the IPO underpricing in China’s stock market and whether the proxies derived from these theories and hypothesis are associated with the degree of IPO underpricing. In addition, the different pricing methods are also added as the explanatory variables in the model. And I expect to find the different pricing methods are associated with different level of IPO underpricing. Using the data of 1129 companies listed on the China’s A share market from 1st January 1996 to 31st December 2008, I find the IPO underpricing is still very high with the initial return is 123.51% and the market-adjusted initial return is 122.24%. Underpricing is correlated with the time elapsed between issuing and listing , the offer size, the fraction of tradable shares , P/E ratio of IPOs, the odds of winning the lottery and the cumulative market return 30 days before IPO. Expect for underwriter reputation, winner’s curse, ex-ante uncertainty, signalling model, cascade hypothesis are able to explain IPO underpricing in a certain context. Furthermore, the different pricing method indeed present different influences on IPO underpricing. although only the cumulative price inquiry method presents a significant relationship.